Immunotherapy in hepatocellular carcinoma: How does underlying liver disease influence therapeutic strategy and outcomes?. (6th January 2023) - Roth, Gael S.; Villeret, François; Decaens, Thomas; Merle, Philippe; Nahon, Pierre
Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer death worldwide, with up to 90% of HCC cases occurring in the setting of underlying cirrhosis. Therapeutic landscape for advanced HCC has dramatically changed in recent years with the advent of immunotherapy, including several combinations. Data suggest that the surrounding liver milieu may influence tumour response. In addition, different aetiologies of HCC and their effects on the host liver may impact response to immunotherapy. However, to date, guidelines do not take into account this parameter to guide therapeutic selection, and phase III trials are likewise performed in patients irrespective of HCC aetiology. Moreover, most clinical trial data are collected in highly selected patients with preserved liver function (defined as Child‐Pugh class A) and controlled portal hypertension, which does not accurately reflect routine clinical practice. In this review, we discuss the influence of liver disease aetiology on the response to immunotherapy in patients with advanced HCC. We also discuss the safety and efficacy of various immunotherapeutic agents in Child‐Pugh B patients to determine if these treatments are beneficial in this vulnerable patient population.